"Everything looks the same": wayfinding behaviour and experiences of stroke inpatients in rehabilitation clinics. Issue 1 (31st December 2022) - Kevdzija, Maja
ABSTRACT: Purpose: To examine stroke inpatients' real-life wayfinding behaviour and how the built environment of rehabilitation clinics might influence their behaviour and experiences. Methods: Stroke inpatients in seven rehabilitation clinics were observed (n = 70), each over the course of 12 consecutive hours. Their paths through the clinic and the locations of encountered wayfinding-related events were mapped on the floor plans and described in the written notes. The observations were supplemented by a survey asking patients about their wayfinding experiences. Results: For a third of observed patients, at least one wayfinding-related event was observed on the observation day, and 50% of patients reported getting lost in their clinic at least once. Most wayfinding-related events occurred between patient rooms and therapy rooms, and patients frequently relied on backtracking or the help of the staff to find their way. Clinics' layout organization was found to play a role in the wayfinding behaviour of patients. Conclusions: Wayfinding is a common challenge that stroke inpatients encounter in rehabilitation clinics. Avoiding multiple decision nodes on the paths between patient rooms and therapy rooms and creating distinct identities for corridor segments in the decision nodes and the areas in front of elevators would likely improve wayfinding performance.